Mycoremediation for decolorization of dye in wastewater using fungi consortium culture: a review / Nasrul Nafis Ibrahim …[et al.] - Ismail, Hasnun Nita; Lokman, Nurul Fariha; Tay, Chia Chay; Ibrahim, Nasrul Nafis (Universiti Teknologi MARA, 2021)
Dye is extensively used in industries, such as textile, paper printing, food, and leather. Dye causes significant effects on living organisms and the environment. Current dye treatment methods are inefficient in decolorization as the dye is highly persistent. Efficiency in the decolorization of dye is a challenge for industries as well as for wastewater treatment systems. This paperfocuses on the mycoremediation dye treatment method, a sustainable treatment method that leads to green technology. This study explores mycoremediation efficiency and processes for dye decolorization. The gap of study on fungal mixed culture shapes future study direction of dye decolorization. Synergistic or antagonistic effects of mixed culture towards dye decolorization should be further investigated.